Forest flammability in Volyn and Zhytomyr Polissia - Андреєва , О. Ю.; Сидоренко , С. Г.; Мартинчук , І. В. (Forestry and Forest Melioration, 2023)
Introduction In recent decades, the frequency and area of forest fires have increased in different regions of the world, particularly in Ukrainian Polissia. The natural fire hazard is assessed by considering forest characteristics, the distribution of ignition sources, and weather variables. The Fire Weather Index (FWI) has been proposed to assess fire hazards in Canadian forests. FWI considers the initial spread index (ISI) and the build-up index (BUI), which consider the influence of the moisture of combustible materials upon the fire behavior at the current temperature, relative humidity, wind speed, rainfall, etc. The aim of the research was to identify the features of the flammability in forests of Volyn, Zhytomyr, and Rivne regions, and to evaluate the relations between the number of fires and the burnt area with climatic indices, particularly FWI. Materials and Methods The materials of the statistical reporting of the State Forest Resources Agency of Ukraine on the number of fires and burnt areas in the forest fund of Zhytomyr, Volyn, and Rivne regions were used. In each region, the absolute flammability was evaluated as the average annual number of fire incidents per 1,000 ha of forested areas and per 1,000 ha of pine stands. The relative flammability was evaluated by the average annual fire area in hectares per 1,000 ha of forested areas and per 1,000 ha of pine stands. Air temperature and precipitation indices for individual months were obtained from the weather stations in Zhytomyr, Rivne, and Lutsk for 2007–2020 in the databases https://climatecharts.net/. Based on these data, the average values of temperature and precipitation for the year and the growing season as well as the hydrothermal coefficient according to G.T. Selyaninov were evaluated. The FWI value was obtained in the GSFC DAAC global network for the coordinates of meteorological stations in each administrative region and averaged over months and years. The dependence of a number of fire incidents and burnt areas on weather indices was assessed using the Spearman criterion. Results and Conclusions It was found that the average annual number of fires in 2007–2020 was 21.5 ± 8.68; 29.1 ± 6.34 and 99.2 ± 35.96 cases in the forest fund of Volyn, Rivne, and Zhytomyr Regional Forest and Hunting Management Administrations (RFHMA), respectively. The average fire area was the smallest in the forest fund of the Volyn RFHMA (26.4 ha), and the largest one was found in the forest fund of the Zhytomyr RFHMA (3,214.6 ha). Fire peaks were observed in 2009, 2015, and 2020. These years had the highest number of fires and burnt areas (99.2 cases and 3,214.6 ha, respectively). The maximum FWI values in Lutsk and Rivne were noted in 2009, 2011, 2015, and 2019, and in Zhytomyr in 2015 and 2020. In all regions, FWI had increased by 2022. The most significant negative relationship was found between the burnt area and indices associated with moisture deficit (precipitation, hydrothermal coefficient, and FWI). 3 Figs., 4 Tables, 29 Refs.